Effects of Salusin‐β on action potential and ionic currents in ventricular myocytes of rats. (4th September 2012) - Ren, An‐Jing; Liang, Qing; Wang, Rong; Ji, Hai‐Yu; Wu, Yi; Shi, Jing‐Song; Lin, Li; Yuan, Wen‐Jun
Abstract: Aim: Salusin‐β is a regulatory peptide that exerts negative inotropic effect on ventricular muscle, but its electrophysiological effects on ventricular myocytes are still unknown. Methods: Action potential and channel currents such as sodium current ( I N a ), transient outward potassium current ( I to ), steady‐state potassium current ( I sus ), sodium–calcium exchange current ( I N aCa ) and inward rectifier potassium current ( I K 1 ) were measured in ventricular myocytes isolated from 12 to 16 weeks rats by whole‐cell voltage‐clamp techniques. Results: Salusin‐β dose‐dependently shortened the duration of action potential in rat ventricular myocytes. Furthermore, salusin‐β significantly inhibited I N aCa and increased I to, but did not affect I N a, I sus and I K 1 . Conclusion: These results suggest that the effect of salusin‐β on action potential may be partly attributed to a decrease in inward currents and an increase in outward currents.